Differential Expression of MicroRNAs in the Colorectal Serrated Neoplasia Pathway and Adenoma–Carcinoma Sequence - Takashi Murakami; Hiroyuki Mitomi; Naoki Tsugawa; Yudai Otsuki; Eiji Kamba; Yuichiro Kadomatsu; Takuo Hayashi; Tsuyoshi Saito; Tomoyoshi Shibuya; Takashi Yao; Akihito Nagahara (Gastroenterology Research and Practice)
Conclusions: These findings indicate that the SSL and AD pathways exhibit distinct miRNA expression dynamics during colorectal tumorigenesis, with the AD lineage showing a progressive increase in oncogenic miRNAs and the SSL series exhibiting selective downregulation or plateauing, particularly in invasive lesions. The differential expression of miR-20a, miR-21, miR-93, and miR-181b was presumed to be related to (epi)genetic alterations among serrated neoplasia and AD–carcinoma routes.